A Rare Case Report of Acrania (Journal of National Institute of Neurosciences Bangladesh, 2024)
Acrania is a rare congenital anomaly and characterized by partial or complete absence of the calvarium. Although acrania associated with anencephaly is a well-recognized entity but isolated acrania is a rare anomaly.  Ultrasound allows early diagnosis of this anomaly. The fetus was found to have a completely formed brain, base of the skull and facial structures but lacking a cranium.  Authors present a rare case of acrania. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):157-160